2018
DOI: 10.1109/tvt.2017.2775249
|View full text |Cite
|
Sign up to set email alerts
|

Geolocation-Based Access for Vehicular Communications: Analysis and Optimization via Stochastic Geometry

Abstract: Delivery of broadcast messages among vehicles for safety purposes, which is known as one of the key ingredients of Intelligent Transportation Systems (ITS), requires an efficient Medium Access Control (MAC) that provides low average delay and high reliability. To this end, a Geo-Location Based Access (GLOC) for vehicles has been proposed for Vehicle-to-Vehicle (V2V) communications, aiming at maximizing the distance of co-channel transmitters while preserving a low latency when accessing the resources. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 40 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…The considered distance-proportional UL power control technique only requires the knowledge of the locations of the BSs, opposed to the truncated channel-inversion power control scheme, that demands further computational resources for the channel estimation. This knowledge can be obtained by monitoring the locations of the BSs through a low-rate feedback channel or by a global positioning system mechanism [30]. For the DL transmissions, we consider a fixed power transmission allocation scheme, i.e.…”
Section: Power Allocationmentioning
confidence: 99%
“…The considered distance-proportional UL power control technique only requires the knowledge of the locations of the BSs, opposed to the truncated channel-inversion power control scheme, that demands further computational resources for the channel estimation. This knowledge can be obtained by monitoring the locations of the BSs through a low-rate feedback channel or by a global positioning system mechanism [30]. For the DL transmissions, we consider a fixed power transmission allocation scheme, i.e.…”
Section: Power Allocationmentioning
confidence: 99%
“…For traditional mmWave networks and vehicular communications, stochastic geometry has already been widely utilized [18,[20][21][22][23][24][25][26][27]. The authors in [20] modeled line-of-sight (LOS) and non-LOS (NLOS) base stations (BSs) as two independent thinning Poisson point processes (PPPs) to evaluate the coverage and rate performance of cellular networks.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…However, in VPSs, the length of one platoon is nonnegligible. To this end, Matérn hard-core process (MHCP) of type II has been investigated in [27]. To simplify the analysis, the authors in [27] regarded MHCP as a stationary thinning PPP, which sacrifices the evaluation accuracy.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…Ye and Zhuang proposed an adaptive control MAC solution that switches between 802.11p and TDMA-based MAC depending on the network load [22]. A study of the periodical broadcast with geolocation-based access in LTE V2X can be found in [23]. It can be seen that these works usually aim to achieve a significant performance improvement at the cost of a larger overhead necessary for implementing an effective coordination in the network.…”
Section: Related Workmentioning
confidence: 99%